2018
DOI: 10.2147/ijn.s188175
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of toxicity of TiO<sub>2</sub>, ZnO, and Ag nanoparticles to human aortic smooth-muscle cells

Abstract: PurposeTo evaluate the adverse vascular effects of nanoparticles (NPs) in vitro, extensive studies have investigated the toxicity of NPs on endothelial cells, but the knowledge of potential toxicity on human smooth-muscle cells (SMCs) is currently limited.MethodsThis study compared the toxicity of TiO2, ZnO, and Ag NPs to human aortic SMCs.ResultsOnly ZnO NPs significantly induced cytotoxicity, accompanied by increased intracellular reactive oxygen species, Zn ions, and endoplasmic reticulum stress biomarkers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 31 publications
(43 reference statements)
3
30
0
Order By: Relevance
“…This is consistent with our recent reports that XFJ14 was not cytotoxic to Caco-2 cells 19 or human aortic smooth muscle cells. 41 Moreover, the results from this study (Figure 5) and our previous studies 19,41 showed that Ag NMs did not significantly induce intracellular ROS, which could explain the lack of cytotoxicity. 3-Hydroxyflavone-induced cytotoxicity as shown by CCK-8 assay did not further enhance the cytotoxicity of Ag NMs (Figure 3).…”
Section: Discussionsupporting
confidence: 57%
“…This is consistent with our recent reports that XFJ14 was not cytotoxic to Caco-2 cells 19 or human aortic smooth muscle cells. 41 Moreover, the results from this study (Figure 5) and our previous studies 19,41 showed that Ag NMs did not significantly induce intracellular ROS, which could explain the lack of cytotoxicity. 3-Hydroxyflavone-induced cytotoxicity as shown by CCK-8 assay did not further enhance the cytotoxicity of Ag NMs (Figure 3).…”
Section: Discussionsupporting
confidence: 57%
“…Nano-TiO 2 , as one of the top five nanoparticles in annual production, is widely applied in industries ranging from healthcare to drug delivery. 3,27 The properties of nano-TiO 2 , such as the minute size, photocatalytic activity, and high biological reactivity, have raised concerns regarding toxicity. UVA, from 315 nm to 400 nm, constitutes the major UV irradiation in sunlight, which penetrates the epidermis and basal germinative layers, and is clearly related to human skin cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This might contribute to the vasculatory disorders during nano-TiO 2 exposures. [13,63] Impairment of the endothelium-dependent vasodilation in the fetal aorta, the coronary arterioles and mitochondrial dysfunction have also been found in the offspring of the nano-TiO 2 -exposed female rats. [64,65] The cardiac contractile dysfunction in the offspring of mice gestationally exposed to nano-TiO 2 was a result of the oxidative stress and inflammation in the heart as well as the direct effects on the fetal vasculature.…”
Section: Circulatory and Cardiovascular Systemmentioning
confidence: 99%